Is tele-diagnosis of dental conditions reliable during COVID-19 pandemic? Agreement between tentative diagnosis via synchronous audioconferencing and definitive clinical diagnosis - Shaymaa Abdulreda Ali (17563116) (2022)
Objectives To assess the reliability of synchronous audioconferencing teledentistry (TD) in making tentative diagnosis compared to definitive clinical face-to-face (CFTF) diagnosis; and whether agreement was influenced by dentist's experience, caller-patient relationship, and time of call. Methods All patients calling the TD hotline during COVID-19 pandemic, triaged as emergency/ urgent and referred for CFTF care were included (N=191). Hotline dentists triaged the calls, made tentative audio-dentistry (AD) diagnosis, while dentists at point of referral made the definitive CFTF diagnosis. Cohen's weighted kappa (κ) assessed the extent of agreement between AD vs CFTF diagnosis. Results There was significantly very good pair-wise agreement (κ = 0.853, P < 0.0001) between AD and CFTF diagnosis. AD diagnosis of pulpitis and periodontitis exhibited the most frequent disagreements. Tele-dentists with ≥ 20 years’ experience exhibited the highest level of agreement (κ =0.872, P < 0.0001). There was perfect agreement when mothers mediated the call (κ = 1, P < 0.0001), and very good agreement for calls received between 7 am-2 pm (κ = 0.880, P < 0.0001) compared to calls received between 2-10 pm (κ = 0.793, P < 0.0001). Conclusions Remote tentative diagnosis using AD is safe and reliable. Reliability was generally very good but varied by dentist's experience, caller-patient relationship, and time of call. Clinical significance The findings suggest that using AD in the home environment is safe and reliable, deploying providers with variable years of experience. The findings have generalizability potential to a variety of similar circumstances, healthcare settings and epi/pandemic situations. Other Information Published in: Journal of Dentistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jdent.2022.104144